Head-mounted display-based (HMD) vs desktop-based (DB) virtual reality anatomy: a preliminary usability study - Zamli, Zaitunnatakhin; Ramli, Rohaini; Sulaiman, Hidayah; Che Azemin, Mohd Zulfaezal; Wan Salleh, Wan Muhamad Salahudin; Yusof, Nurul Asyiqin; Mahalil, Imran; Mohd. Yusof, Azmi (National University of Singapore, 2025)
Introduction: Virtual reality (VR) has been widely used in medical and health sciences education since the late twentieth century. VR complements the conventional teaching and learning (T&L) approach by providing an engaging and immersive 3D spatial learning environment, especially for understanding the orientation of anatomical structures. Despite these advantages, the usability and student preference of highly immersive head-mounted display-based (HMD) and less immersive desktop-based (DB) VR in human anatomy courses have yet to be determined.